How to describe concentration quenching in rare earth doped semiconductors. Issue 1 (29th November 2012) - Benz, Felix; Guerra, J. Andrés; Weng, Ye; Weingärtner, Roland; Strunk, Horst P.
Abstract We report on two approaches to describe concentration quenching of rare earth doped semiconductors. The examples used are terbium doped aluminium nitride and silicon carbide. The aim of the presented work is to introduce a frame of description that can be used to analyse experimental results. The first approach, a rate equation based model, uses mean values for both the transition probabilities and the centre interdistance. The second approach, an atomistic Monte‐Carlo simulation, is capable of describing single centres and thus can handle different spatial distributions of the centres. Both models describe the experimentally observed concentration quenching effects. The Monte‐Carlo simulation is more appropriate since it can handle microstructural influences like clustering or precipitation of the rare earth ions. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)